Genetic Epidemiological Studies of Hearing Loss in Faisalabad City, Pakistan (Global Journal of Medical Research, 2014)
Basic aim of the study was to investigate the incidence, prevalence, disease pattern and the etiology of the non-syndromic congenital deafness in a selected population from different areas and schools for special education of Faisalabad District, Pakistan. An epidemiological study was carried out through a questionnaire including different standard parameters like surname, parental marriage age, parental relationship of marriage, their family history including information about number of offspring, sex, birth order, number of normal and diseased individuals and age of onset. Information about economic status and educational qualification of parents, their locality, food habits and paternal smoking or non-smoking habits were also recorded. In a total of 436 deaf cases, 55.0% were males and 44.95% were females while 22 families were selected for pedigree analysis. Urban population (79.58%) was affected more than rural population (20.41%). Mean maternal and paternal marriage age was 20.63 ± 0.163 and 24.989 ± 0.217, respectively with smaller (0-4 years) marriage age difference.
Keywords: epidemiology; deafness; inheritance; pedigree